Demograficzne starzenie się populacji jako wyzwanie dla samorządu gminnego – doświadczenia gmin województwa pomorskiego - Richert-Kaźmierska, Anita (Polityka i Społeczeństwo, 2020)
Population aging is a natural social process. Nevertheless the increase in the population of the elderly (including those of an advanced age – above 85 years old) in the last decade in Poland is unusually high. The rapid increase in the number of older people and their percentage in the total population is associated with specific social and economic consequences. These have to be faced both by the central government as well as local authorities. In the article author concentrated on the question of the knowledge of local authorities about demographic changes and perceptions of their consequences. The aim of the study was to assess the level of knowledge of local government representatives on the ageing of the local community and the interpretation of changes caused by this process. In addition, the author has identified the measures that local governments have declared to undertake to increase awareness of aging and its consequences. In the article the results of a survey conducted in July 2015 in 77 of the 119 non-metropolitan municipalities of Pomeranian province has been used.